Cytogenetics of wheat-Thinopyrum hybrids and derivates - Littlejohn, Gail M.(Gail Margaret) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1992.